Metabolomics in early life and the association with body composition at age 2 years. Issue 3 (13th October 2021) - van Beijsterveldt, Inge A.L.P.; Snowden, Stuart G.; Myers, Pernille Neve; de Fluiter, Kirsten S.; van de Heijning, Bert; Brix, Susanne; Ong, Ken K.; Dunger, David B.; Hokken‐Koelega, Anita C.S.; Koulman, Albert
Summary: Background and Objectives: Early life is a critical window for adiposity programming. Metabolic‐profile in early life may reflect this programming and correlate with later life adiposity. We investigated if metabolic‐profile at 3 months of age is predictive for body composition at 2 years and if there are differences between boys and girls and between infant feeding types. Methods: In 318 healthy term‐born infants, we determined body composition with skinfold measurements and abdominal ultrasound at 3 months and 2 years of age. High‐throughput‐metabolic‐profiling was performed on 3‐month‐blood‐samples. Using random‐forest‐machine‐learning‐models, we studied if the metabolic‐profile at 3 months can predict body composition outcomes at 2 years of age. Results: Plasma metabolite‐profile at 3 months was found to predict body composition at 2 years, based on truncal: peripheral‐fat‐skinfold‐ratio (T:P‐ratio), with a predictive value of 75.8%, sensitivity of 100% and specificity of 50%. Predictive value was higher in boys (Q 2  = 0.322) than girls (Q 2  = 0.117). Of the 15 metabolite variables most strongly associated with T:P‐ratio, 11 were also associated with visceral fat at 2 years of age. Conclusion: Several plasma metabolites (LysoPC(22:2), dimethylarginine and others) at 3 months associate with body composition outcome at 2 years. These results highlight the importance of the first months of life for adiposity programming.